The Spirit of Colonial Williamsburg : Ghosts and Interpreting the Recreated Past - Pirok, Alena, 1988- (Book collections on Project MUSE., 2022)
"On any given night, hundreds of guests walk the darkened streets of Colonial Williamsburg looking for ghosts. Since the early 2000s, both the museum and private companies have facilitated these hunts, offering year-round ghost tours. Critics have called these excursions a cash grab, but in truth, ghosts and hauntings have long been at the center of the Colonial Williamsburg project. The Spirit of Colonial Williamsburg examines how the long-dead past comes alive at this living-history museum. In the early twentieth century, local stories about the ghosts of former residents-among them Revolutionary War soldiers and nurses, tavern owners and prominent attorneys, and enslaved African Americans-helped to turn Williamsburg into a desirable site for historical restoration. But, for much of the twentieth century, the museum tried diligently to avoid any discussion of ghosts, considering them frivolous and lowbrow. Alena Pirok explores why historic sites have begun to embrace their spectral residents in recent decades, arguing that through them, patrons experience an emotional connection to place and a palpable understanding of the past through its people"--